The Management of Vocational Subject Teachers at SMK Sekolah Indonesia Kota Kinabalu (SIKK) Sabah-Malaysia: An Analysis of Availability, Adaptive Strategies, and Challenges of Overseas Vocational Education - Hildayanti Hildayanti; Cepi Safruddin Abdul Jabar (MASI Mandiri Edukasi, 2026)
The management of productive teachers in vocational schools faces significant challenges, particularly in cross-border educational institutions that experience limitations in human resources, recruitment authority, and professional development opportunities. This study aims to analyze the management of productive teachers at SMK Sekolah Indonesia Kota Kinabalu, focusing on planning, recruitment, professional development, performance evaluation, compensation, and termination, and to identify adaptive strategies grounded in organizational resilience theory. This research employed a qualitative case study design. Data were collected through in-depth interviews with the principal, program coordinators, productive teachers, and adaptive teachers, complemented by participatory observation and document analysis. The data were analyzed using Miles and Huberman's interactive model. The findings reveal that the management of productive teachers faces multiple constraints, including mismatches in workforce planning, recruitment limitations, restricted professional development, suboptimal performance evaluation, and inadequate compensation systems. To address these challenges, the school implements adaptive strategies such as involving adaptive teachers, inviting industry practitioners as guest instructors, and establishing partnerships with business and industrial sectors. This study concludes that adaptive teacher management grounded in organizational resilience is essential to sustain the quality of vocational education and recommends strengthening data-driven human resource systems, continuous capacity-building programs, and strategic industry collaboration.